ANALISIS PUTUSAN NOMOR 60/PDT.SUS.HAK CIPTA/2020/PN. NIAGA JKT PST ATAS PERLINDUNGAN HUKUM PEMEGANG HAK CIPTA PROGRAM KOMPUTERANALYSIS OF DECISION NUMBER 60/PDT.SUS. COPYRIGHT /2020/ PN.NIAGA JKT PST ON LEGAL PROTECTION OF COMPUTER PROGRAM COPYRIGHT HOLDERS: Analysis of Decision Number 60/Pdt.Sus. Copyright /2020/ PN.Niaga Jkt Pst on Legal Protection of Computer Program Copyright Holders - Jamlean, Rozikin (Jurnal Globalisasi Hukum., 2024)
Along with the development of technology, the importance of legal protection to anticipate legal violations of copyright, the author takes the formulation of this research problem (1) How is the legal protection of the copyright of the CXM application computer program recorded by other parties without the permission of the copyright holder in case No. 60/Pdt.Sus.Copyright/2020/PN.Niaga Jkt Pst? This research uses normative legal research. Analysis The copyright protection of the CXM computer program, in this case, written by a third party without a license to the copyright owner is based on article 97 paragraph (1) of the Copyright Act, and the plaintiff claims to be the original copyright owner. Since you are the creator of the CXM application, the plaintiff is the owner of the application. It is stated that the business registration number titled Customer Service Management System number 000116753 created in the name of the defendant is incorrect, because the CXM application was first filed, published and distributed by the plaintiff for the first time, the plaintiff requests that the registration be terminated with the registration number 000116753 and the name specified above as the defendant in the recording of the creation by the Customer Experience Management System and the defendant all legal effects. The co-defendant is also directed to immediately delete the creation registration number 000116753 under the name of Customer Experience Management System which is named by the Defendant at the place of registration